Reforming the Benefit System to 'Make Work Pay': Options and Priorities in a Weak Labour Market - Herwig Immervoll (Institute for the Study of Labor (IZA), 2012)
Policies that support the unemployed, while reducing employment barriers and benefit dependency, are of particular interest in the current economic climate. This paper examines alternative policy approaches for combining adequate income support for the jobless with incentives to keep out-of-work spells short. After summarising the main parameters of existing income support measures for the unemployed in EU and OECD countries, I review evidence on the economic relevance of work incentives and discuss their significance when labour markets are weak during and after an economic downturn. Based on the available evidence, I propose a set of policy priorities to strengthen both the protection and the promotion functions of unemployment support.
Keywords: H31; H53; J08; J68; 330; unemployment benefits; income support; work incentives; activation; Arbeitslosenversicherung; Arbeitsmarktpolitik; Arbeitsangebot; Ökonomischer Anreiz; Aktivierende Arbeitsmarktpolitik; EU-Staaten; OECD-Staaten